2008
DOI: 10.1590/s1516-35982008000800017
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de fontes e formas de processamento do amido sobre o desempenho e o metabolismo do nitrogênio em vacas Holandesas em lactação

Abstract: RESUMO -Avaliou-se a influência das fontes e formas de processamento do amido utilizado na dieta sobre o desempenho e o metabolismo do nitrogênio em vacas Holandesas em lactação alimentadas com cana-de-açúcar como volumoso. Utilizaram-se cinco vacas pluríparas, canuladas no rúmen e no duodeno, distribuídas em quadrado latino 5 × 5.As rações foram compostas de 40% de cana-de-açúcar e 60% de concentrado e diferiram quanto ao processamento ou à fonte principal de amido: milho moído grosso; milho moído fino; milho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
1
7
2
2
Order By: Relevance
“…Plasma glucose levels showed a quadratic effect as the corn was replaced by WCSEd (Fig. 1a), differing from the results observed by Pires et al (2008), who found no significant changes in plasma glucose concentrations in animals fed with cassava chips as a source of starch. The glucose levels stayed within the appropriate levels for cattle, which can range from 45 to 75 mg dL -1 (Fernandes et al 2012).…”
contrasting
confidence: 92%
“…Plasma glucose levels showed a quadratic effect as the corn was replaced by WCSEd (Fig. 1a), differing from the results observed by Pires et al (2008), who found no significant changes in plasma glucose concentrations in animals fed with cassava chips as a source of starch. The glucose levels stayed within the appropriate levels for cattle, which can range from 45 to 75 mg dL -1 (Fernandes et al 2012).…”
contrasting
confidence: 92%
“…According to Santos et al (1998), as the degradability of the starch increases, there is an increase in protein content in the milk, perhaps due to the increase of microbial synthesis, leading to an increase in the metabolizable protein flow to the intestine, improving the profile of essential amino acids. These results disagree with those reported by Pires et al (2008), they found that the conversion efficiency from the feed into protein in the milk was lower for the cassava starch, another product with a similar composition to SRECS.…”
Section: Resultscontrasting
confidence: 99%
“…This is similar to a report by Pires et al (2008), who found no difference in plasma glucose concentrations in animals fed cassava starch as a source of starch. The plasma concentration of urea did not differ (P>0.05) between treatments, showing that the efficiency of protein utilization was not influenced by the substitution of corn by SRECS.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Menor teor de ureia no plasma indica menores perdas de proteína, ingrediente de maior custo na dieta de bovinos. Ao contrário do atual estudo, Pires et al (2008) verificaram alteração significativa para o teor de ureia plasmática (médias de 21,9; 23,6; 21,3; 21,4 e 27,6mg/dL) em vacas leiteiras alimentadas com milho moí-do grosso, milho moído fino, milho floculado 310g/L, milho floculado 360g/L e raspa de mandioca (28,4% da dieta total), respectivamente.…”
Section: Discussionunclassified